ANALISIS SENYAWA FITOSTEROL Cymbopogon citratus dan Curcuma longa SEBAGAI ANTIALZHEIMER - Bare, Yohanes (Program Studi Pendidikan Biologi FKIP Unpatti, 2021)
Background: Alzheimer is a disease with decreased episodic memory function and cognitive function. Thetreatment system is carried out by inhibiting the performance of genes that have an Alzheimer's stimulus function.Alzheimer sufferers have a component that functions as a cholin stimulator and Acetyl CoA isAcetylcholintransferase. Treatment is done by inhibiting Acetylcholintransferase with Cymbopogon citratus andCurcuma longa. The purpose of this study was to analyze the potential phytoserol content of Cymbopogoncitratus and Curcuma longa as anti-AlzheimerMethods: The method used is the in-silico study approach. Protein Acetylcholintransferase (2fy3) was obtainedfrom Protein Data Bank (PDB). The three-dimensional structure of phytosterol compounds identified inCymbopogon citratus and Curcuma longa were downloaded from the PubChem database. Proteins and bioactivecompounds were prepared sequentially using the Discovery studio ver 19.0.0 and the PyRX 0.8 program.Proteins and compounds were interacted with the PyRX 0.8 program and analyzed using the Discovery Studiover.21.1.0 softwareResults: The results showed that the phytoserol content of Cymbopogon citratus and Curcuma longa (1,8Cineole, 3,7-dimethyl-1,3,6-octatriene, Champene, Decanal Selina-6-en-4-ol, Zingiberene) inhibited the activeside of acetylcholinesterase by inhibiting acetylcholinesterase bind amino acid residues through essential oils.This inhibition directly stops the hydrolysis process of acetylcholine into cholin and acetyl CoA so that it canprevent damage to brain cells.Conclusion: The phytoserol content of Cymbopogon citratus and Curcuma longa is predicted to have potentialas anti-Alzheimer through inhibition of Acetylcholintransferase